Founding Workshop for the Advanced Cassava Research Network (1988, Cali, Colombia). Report (International Center for Tropical Agriculture, 1989)
The creation of an advanced cassava research network, through the identification of key constraints in cassava production and processing that could be managed through a multidisciplinary, interrelated network approach, was discussed at this workshop. Priorities were set and potential projects that would benefit all members of the network were explored. Specific research strategies which could conceivably be implemented to resolve these constraints were assessed. (CIAT)